2017
DOI: 10.1007/s12671-017-0686-1
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Mindfulness Intervention Attenuates Desire to Escape Following Experimental Induction of the Interpersonal Adversity Implicated in Suicide Risk

Abstract: According to the interpersonal theory of suicide, perceived burdensomeness and thwarted belongingness are proximal causal factors underlying suicidal desire. The current study examined whether a brief mindfulness intervention can attenuate the deleterious effects of these interpersonal factors on desire to escape, a potential antecedent to suicide risk. Participants (N = 92) completed a computerised team task designed to manipulate perceived burdensomeness and thwarted belongingness (high or low PB/TB) and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“…The interpersonal persistence task (Collins et al, ) provides an opportunity to safely manipulate the interpersonal risk factors thought to be proximal and causal antecedents to suicidal desire to observe the effect on the desire to escape this adversity. Consistent with previous research using this task, we found reliable and large effects of PB‐TB condition on participants’ desire to escape from this interpersonal adversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The interpersonal persistence task (Collins et al, ) provides an opportunity to safely manipulate the interpersonal risk factors thought to be proximal and causal antecedents to suicidal desire to observe the effect on the desire to escape this adversity. Consistent with previous research using this task, we found reliable and large effects of PB‐TB condition on participants’ desire to escape from this interpersonal adversity.…”
Section: Discussionmentioning
confidence: 99%
“…One potential limitation in the design is that we did not include indices of general negative affect measured across the task to demonstrate specificity of the changes in belongingness and burdensomeness. However, previous research using this paradigm found that the desire to drop out of the task is attributable to the specific interpersonal adversity rather than negative affect associated with a general failure experience (George et al, ), and when levels of general negative affect were tracked throughout the task, it was the interpersonal adversity of perceived burdensomeness and thwarted belongingness that predicted the desire to drop out of the task, and not general distress (Collins et al, ).…”
Section: Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Team task belongingness ratings were reverse-coded such that high scores represent higher levels of thwarted belongingness. Recent research indicates that participants who play the Persistence Task express a strong desire to belong to their team, and the large effect of the experimental belongingness manipulation shows that this powerful need to belong to the team can be thwarted(Collins, Stebbing, Stritzke, & Page, 2017).…”
mentioning
confidence: 99%